Edukasi Kelas Ibu Hamil Dalam Meningkatkan Literasi Kesehatan dan Kepatuhan Pemeriksaan Antenatal Care (ANC): Systematic Literature Review - Riyani Muhammad; Hasna Muhammad (Peneliti.net, 2024)
Maternal mortality in Indonesia remains largely attributable to pregnancy- and childbirth-related complications, many of which can be prevented through early detection during antenatal care (ANC). Low health literacy among pregnant women has been associated with poor adherence to recommended ANC visits. The Pregnant Women Class is a group-based educational program initiated by the Indonesian Ministry of Health to improve pregnant women’s knowledge and preparedness for pregnancy and childbirth. This systematic review aimed to synthesize empirical evidence on the effects of Pregnant Women Class education on improving health literacy and adherence to ANC visits. A literature search was conducted using national academic databases and search engines, including Google Scholar, Garuda/Portal Garuda, and health journal repositories, using combinations of the keywords “pregnant women class,” “health literacy,” “pregnant women’s knowledge,” and “antenatal care adherence.” Study selection followed the PRISMA framework, with inclusion criteria comprising quantitative studies (cross-sectional and quasi-experimental designs) published in Indonesian or English between 2021 and 2024. Twelve studies met the inclusion criteria. Most studies (9 of 12) reported a significant association or effect between participation in Pregnant Women Classes and/or health literacy levels and increased knowledge and/or ANC adherence. One study reported a non-significant finding, suggesting the influence of other factors, such as family support and accessibility of healthcare facilities. Education delivered through Pregnant Women Classes was consistently positively associated with improved health literacy among pregnant women; however, its effect on ANC adherence was not always direct and appeared to be moderated by social and environmental factors. Further research using controlled experimental designs and larger sample sizes is needed to strengthen the evidence for causal relationships.